Deradikalisasi Remaja dan Perspektif Mereka terhadap Radikalisme - Cecep Anwar; Ujang Dedih (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
Radical actions can be carried out by various community groups, especially those with low religious and national understanding. The purpose of this study was to examine how the program and the results of the program of Islamic Spiritual Organizations at SMK in an effort to deradicalize, and how the results of student understanding related to radicalism. The methodology used is descriptive-qualitative method, which is trying to obtain a factual picture of the implementation of Islamic Spiritual activities at SMK and MA in Sukabumi. Subject Students are members of Rohis at SMK and MA in Sukabumi Regency. One IT Vocational High School in Sukabumi Regency and one private MA in Sukabumi were selected. The technique of collecting data through observation, interviews, and distributing questionnaires, obtained 31 respondents who filled out the questionnaire. The results showed that there were no seminars related to the theme of deradicalization, the Rohis program was only routine religious activities, such as recitations, celebrations of religious holidays and regular studies so that all respondents needed an understanding of deradicalization in order to stay away from radicalism. What is wrong regarding radicals is definitely terrorists even though that is not the case, students only know that there is intolerance, ethnicity, religion, and race issues between groups as triggers for radical actions. Tindakan radikal bisa dilakukan oleh berbagai kelompok masyarakat, terutama yang pemahaman keagamaan dan kebangsaannya rendah. Tujuan penelitian ini adalah untuk mengkaji bagaimana program dan hasil program organisasi Rohani Islam SMK dalam upaya deradikalisasi, dan bagaimana hasil pemahaman siswa terkait radikalisme. Metodologi yang dipergunakan adalah metode deskriptif-kualitatif, yakni berusaha memperoleh gambaran faktual tentang pelaksanaan kegiatan Rohani Islam pada SMK dan MA di Sukabumi. Subjek Siswa anggota Rohis pada SMK dan MA di Kabupaten Sukabumi. Terpilih satu SMK IT di Kabupaten Sukabumi dan satu MA swasta di Sukabumi. Teknik mengumpulkan data melalui observasi, wawancara, dan penyebaran angket, diperoleh 31 responden yang mengisi angket. Hasil penelitian menunjukkan bahwa belum ada dan belum pernah ada seminar terkait tema deradikalisasi, program Rohis hanya kegiatan keagamaan rutin, seperti pengajian, perayaan hari besar keagamaan dan kajian rutinan sehingga seluruh responden membutuhkan pemahaman tentang deradikalisasi agar terjauh dari radikalisme, menurutnya selama ini ada cara pandangan yang salah terkait orang radikal pasti teroris padahal bukan itu, siswa baru tahu bahwa adanya intoleran, masalah suku, agama, dan ras antar golongan sebagai pemicu tindakan radikal.